Predictors of clinical outcomes of self-expandable metal stent treatment for malignant colorectal obstruction: A Honam Association for the Study of Intestinal Disease (HASID) multicenter study. Issue 27 (9th July 2021) - Han, Bora; Hong, Ji-Yun; Myung, Eun; Oh, Hyung-Hoon; Yang, Hee-Chan; Kim, Sang-Wook; Lee, Jun; Kim, Seong-Jung; Han, Yeom-Dong; Seo, Geom-Seok; Hong, Gun-Young; Kim, Ho-Dong; et al.
Abstract : Abstract: There has been increased use of self-expandable metal stents (SEMS) in treating malignant colorectal obstruction (MCO). The aim of this study was to investigate factors that are associated with the outcomes of SEMS placement for MCO. Clinical data from patients who underwent SEMS placement for MCO at 6 hospitals in Honam province of South Korea between 2009 and 2018 were reviewed retrospectively. Eight hundred two patients were identified and their data were analyzed. Technical success, clinical success, complications, and predictors of outcome were included as main outcome measures. Technical and clinical success rates were 98.8% (792/802) and 90.1% (723/802), respectively. Complications including stent migration, stent occlusion due to tumor ingrowth and outgrowth, perforation, bacteremia/fever, and bleeding occurred in 123 (15.3%) patients. In multivariate regression analyses, procedure time was significantly associated with the technical success of SEMS placement ( P = .001). Longer length of obstruction, the use of covered stent, and longer procedure time were significant independent predictive factors for the clinical success of SEMS placement (odds ratio [OR] 0.974 (95% confidence interval [CI] 0.950–0.990); P = .043, OR 0.255 (95% CI 0.138–0.471); P < .001, and OR 0.957 (95% CI 0.931–0.984); P = .002, respectively). Stage IV colorectal cancer and the use of covered stent were significant independent predictive factors for the development of complications after SEMS placement (OR 2.428 (95% CI 1.407–4.188); P = .001 and OR 3.329 (95% CI 2.060–5.378); P < .001, respectively). Longer length of obstruction, the use of covered stent, and longer procedure time were associated with lower clinical success rates. Having stage IV colorectal cancer and the use of covered stents were associated with an increased risk of complications.